Competence-Based System Self-Study System for Suggesting Study Materials Links. (March 2014) - Nitchot, Athitaya; Gilbert, Lester; Wills, Gary B.
The article proposes a self-study system which suggests web links to learners. The suggestions depend upon the learner's chosen competences selected from a competence structure for a particular knowledge domain. Three experiments were conducted, where the first compared the perceived usefulness and value of the links generated by different learning paths selected to navigate the competence structure. The second experiment evaluated the acceptability of the self-study system, and the third experiment compared ratings of the links generated by two different search engines (Google, iSEEK). The results showed that the competence-based self-study system was accepted by learners, that learning paths which included more competence nodes were more useful than paths with fewer nodes, and that there was no significant difference between the ratings of the competence-based links generated by the two types of search engine.